Stylized rhythmic music to build up vocabulary in students of tenth grade at Unidad Educativa Liceo Cristiano Peninsular. La Libertad, province of Santa Elena. School year 2015-2016. - Roca Panimboza, Julio Andres (2015)
The main aim of this project is to build up vocabulary by implementing stylized rhythmic music to students of tenth grade at Unidad Educativa Liceo Cristiano Peninsular. This research paper was supported by theoretical framework, interviews, focus group, diagnostic test, and the implementation of the proposal. Teenagers sometimes are difficult to cope with, but there is one possibility to direct them to the learning without boring them. The stylized rhythmic music well known as hip-hop music has played an important role in the development of this project. Before the implementation, the environment of the class was tense because there were not any of those activities that activate them to learn this language. once the proposal was applied, students changed their behavior and started being part of the process; and as a result, the acquisition of english words was meaningful. Therefore, it can be asserted that utilizing stylized rhythmic music is one of the strategies to build up vocabulary. In the proposal, besides of being used as a motivational aspect to study this language, there are other factors that can be covered. The increase of practicing english was noticeable and if the students are guided for a long period of time, they will finally get astonishing outcome in the building up of the vocabulary.